Занимательная химия. 8-11 кл.: в 2 ч. (И. А. Леенсон) - Леенсон И. А. (1996)
Экземпляры: аб (ретроконверсия) / Инвентарный номер: 33723 / Цена: 14150.00 / Сис.шифр: 24 / Авт.знак: Л 59 / ГРНТИ: 31 / ББК: 24